Managerial Efficiency of Officers and Office Performance of the Department of Agrarian Reform in Northern Negros Occidental - Mabunay, Teresita (Technium Social Sciences Journal, 2023)
The determination of the managerial efficiency of the heads of offices of DAR, particularly in the DAR municipal offices of Northern Negros Occidental, is found to be an imperative need, hence this study. For the establishment of an efficiently running agency, the level of work performance of the offices is also expected to be at par, and so is the necessity of its evaluation in this study. This descriptive research design used a researcher-made survey questionnaire with 87 personnel to answer and help determine the level of managerial efficiency of the 33 MARPOs. As to the work performance of the DAR offices, the same descriptive design was used utilizing document analysis which is the Office Performance and Commitment Review (OPCR) of the MARPOs and a checklist determined the challenges encountered by the agrarian reform offices in Part III of the questionnaire. As a whole, the level of managerial efficiency of the MARPOs is high, indicating that the MARPOs are capable and competent and have demonstrated excellence in performing their functions. Positively, the result of a high level of managerial efficiency is exhibited by the MARPOs in the discharge of their official functions and outstanding performance of the DARMOs over the years.